Lymphocytes as an Indicator for Initial Kidney Function: A Single Center Analysis of Outcome after Alemtuzumab or Basiliximab Induction - Annemarie Weissenbacher; Theresa Hautz; Michael Kimelman; Rupert Oberhuber; Hanno Ulmer; Claudia Bösmüller; Manuel Maglione; Stefan Schneeberger (Journal of Immunology Research)
Alemtuzumab, an anti-CD52 T-cell and B-cell depleting monoclonal antibody, is established for induction therapy in renal transplantation (KTx). We herein provide a comparative analysis between alemtuzumab and basiliximab induction therapy and correlate lymphocyte depletion and recovery with the clinical course after KTx. This is a single center retrospective analysis of 225 patients/consecutive kidney transplantations treated with alemtuzumab for lymphocyte depletion and 205 recipients treated with basiliximab. Mean lymphocyte counts were 22.8 ± 9.41% before Tx and 2.61 ± 3.11% between week 1 and week 3 in the alemtuzumab group and 23.77 ± 10.42% before Tx and 13.92 ± 8.20% in the basiliximab group. Delayed graft function (DGF), cytomegalovirus (CMV) status, and recipient age showed a significant correlation with lymphocyte counts in the alemtuzumab group only. The outcome was read in reference to the velocity of lymphocyte recovery and in comparison to the control group. Lymphocyte counts early after transplantation, following alemtuzumab treatment, could be identified as a predictive factor for kidney function early after transplantation. A detailed analysis of phenotype and function of lymphocytes after alemtuzumab induction together with a correlation with the clinical course is warranted.